Degrees at Federal Institutes: what is shown in Brazilian stricto sensu research 2009-2020 (Research, Society and Development, 2022)
As a result of an exercise in the production of the State of Knowledge, in this article we present understandings built on “doing initial teacher training” at Federal Institutes. The objective is to recognize the socio-historical and political-cultural context of the implementation of the offer of initial teacher training courses in the Federal Institutes. To this end, we rely on a set of research produced in Brazil and published in the Biblioteca Digital Brasileira de Teses e Dissertações (BDTD), in the period 2009-2020, on which we incur the recursive sequence of elements and paths of Discursive Textual Analysis (DTA). The analytical process led us to the creation of a space for reconstruction through which understandings linked to two categories emerged: (1) Education Policies and Initial Teacher Training in the FIs and (2) Curricular configurations of Licentiate degrees in the FIs. We recognize, with them, a movement of curricular configurations that both take the deviations from the offer of initial teacher training courses in Brazil as beacons of what is not intended, nor is it wanted for the FIs, as they defend the relationship between theory and practice and the articulation between the different knowledge that make up teaching.